Pregnancy outcomes in prenatally diagnosed 47, XXX and 47, XYY syndromes: a 30‐year French, retrospective, multicentre study. (10th May 2016) - Gruchy, Nicolas; Blondeel, Eleonore; Le Meur, Nathalie; Joly‐Hélas, Géraldine; Chambon, Pascal; Till, Marianne; Herbaux, Martine; Vigouroux‐Castera, Adeline; Coussement, Aurélie; Lespinasse, James; Amblard, Florence; Jimenez Pocquet, Mélanie; et al.
Abstract: Objective: Sex chromosome aneuploidies are frequently detected fortuitously in a prenatal diagnosis. Most cases of 47, XXX and 47, XYY syndromes are diagnosed in this context, and parents are thus faced with an unexpected situation. The objective of the present study was to characterize a French cohort of prenatally diagnosed cases of 47, XXX and 47, XYY and to evaluate the termination of pregnancy (TOP) rate before and after France's implementation of multidisciplinary centres for prenatal diagnosis in 1997. Methods: This retrospective study identified respectively 291 and 175 cases of prenatally diagnosed 47, XXX and 47, XYY between 1976 and 2012. For each case, the indication, maternal age, karyotype and outcome were recorded. Results: Most diagnoses of the two conditions were fortuitous. The occurrence of 47, XXX was associated with advanced maternal age. The overall TOP rate was higher for 47, XXX (22.9%) than for 47, XYY (14.6%), although this difference was not statistically significant. However, the TOP rates fell significantly after 1997 (from 41.1% to 11.8% for 47, XXX and from 25.8% to 6.7% for 47, XYY). Conclusion: The TOP rates after prenatal diagnoses of 47, XXX and 47, XYY fell significantly after 1997, following France's implementation of multidisciplinary centres for prenatal diagnosis. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? 47, XXX and 47, XYY are often detected fortuitously during prenatal diagnosis. The phenotype associated with these conditions does not include severe malformations or psychomotor delay. What Does This Study Add? In France, the termination of pregnancy rates associated with diagnosis of 47, XXX and 47, XYY have fallen over the last few decades. This may be due (at least in part) to better knowledge of these conditions and the introduction of a multidisciplinary approach from 1997 onwards. The foetal incidence of 47, XXX was associated with advanced maternal age.